The Use of the Contra Lateral Latissimus Dorsi Muscle after Forequarter Amputation - a Case Report - Vieira, René Aloisio da Costa (2000)
It reports a case of forequarter amputation due to scapular condrosarcoma. Reconstruction was done with contralateral muscular flap from latissimus dorsi, using secondary pedicle, which has not yet been described for this purpose.